Kinetika Leaching Ni dan Fe dari Bijih Laterit Tipe Limonite Morowali - Prameswara, Gyan; Tyassena, Flaviana Yohanala Prista; Pasaribu, Monita; Febryanzha , Indhyca Novitha (Politeknik ATI Padang, 2022)
Nickel (Ni) deposits are depleting, while demand for the metal is increasing. To address this problem, valuable metals such as Ni and Fe can be extracted from secondary sources such as limonite-type laterite ores. The goal of this study was to investigate the influence of leaching temperature on Ni and Fe recovery, as well as the best kinetic model to represent the leaching process of these metals. Temperature has a considerable impact on the leaching process of Ni and Fe. Increasing the temperature from 30 to 90 oC can increase the recovery of Ni by 50% and Fe by 70 %. Ni and Fe recoveries were highest at 93.21 % and 95 %, respectively. Kinetic analysis of the two metals' leaching processes was also performed. It was discovered that the diffusion process controls Ni leaching, which can be represented using the Zhuravlev kinetic model, whereas chemical reactions on the surface of the unreacted core controls Fe leaching. The activation energies for leaching Ni and Fe are 36.53 and 40.32 kJ/mol, respectively. 1930 exp ((-36.53 kJ/mol)/(R.T))t=[(1-X)-1/3)-1]2 is the kinetic equation for Ni leaching. The kinetic equation for Fe leaching is 3903 exp ((- 40.32 kJ/mol)/(R.T)t=1-(1 X)1/3.